2009
DOI: 10.1021/jf900075h
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Gold Nanoparticle Immunochromatographic Assay (ICG) for the Detection of Zearalenone

Abstract: A monoclonal antibody (mAb)-based gold nanoparticle immunochromatographic assay (ICG) for zearalenone detection was developed, optimized, and validated. The detection limits of ICG optimized with appropriate amounts of zearalenone-bovine serum albumin and gold nanoparticle-mAb to zearalenone were 2.5 ng/mL and 30 μg/kg for the standard solution and spike sample, respectively, and a weak cross-reaction for α-zearalenol and β-zearalenol was observed. The assay required only 15 min to obtain results and one step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 26 publications
1
56
1
1
Order By: Relevance
“…In theory, it is possible to add one or more T-line to an existing LFD and to mix the partner labeled antibodies to increase the number of analytes to be determined. Shim et al (Shim, Kim et al 2009) established a system simultaneously to detect OTA, ZEA, OTA and AFB1 in corn by two LFDs. Additionally, multianalytes detection developed by Kolosova et al (Kolosova, De Saeger et al 2007) also confirmed that two analytes can be simultaneously detected by a single LFIA device (Goryacheva, De Saeger et al 2007).…”
Section: Multi-parametric Immunochromatographic Systemsmentioning
confidence: 99%
“…In theory, it is possible to add one or more T-line to an existing LFD and to mix the partner labeled antibodies to increase the number of analytes to be determined. Shim et al (Shim, Kim et al 2009) established a system simultaneously to detect OTA, ZEA, OTA and AFB1 in corn by two LFDs. Additionally, multianalytes detection developed by Kolosova et al (Kolosova, De Saeger et al 2007) also confirmed that two analytes can be simultaneously detected by a single LFIA device (Goryacheva, De Saeger et al 2007).…”
Section: Multi-parametric Immunochromatographic Systemsmentioning
confidence: 99%
“…In any functionalization efforts with DNA and DNA hybridization, charge screening (salt-aging) was necessary to compensate for the electrostatic repulsion between the negatively charged DNA molecules (Hill and Mirkin 2006 ). Immunochromatographic strip assay 0.32 ng/ml, 2.5 ng/ml Bo et al 2007, Liu et al 2008, Shim et al 2009 Table 1 Summary of the detection sensitivity achieved by gold nanoparticle-based sensor platform.…”
Section: Synthesis/fabrication and Functionalization Of Aunp Probesmentioning
confidence: 99%
“…The color changes associated with NP aggregation, and/or local refractive index change, have been exploited as optical sensing methods for the detection of toxins , Liu et al 2008, Shim et al 2009 ), heavy metals (Darbha et al 2008, Xue et al 2008 ) and other environmental pollutants (Daniel et al 2009, Dasary et al 2009 ) in water, soil and other environmental samples. AuNPs are also being used to enhance the performance of electrochemical sensors due to their catalytic properties (Rassaei et al 2011 ).…”
Section: Application Of Aunps In Detection Of Chemical Pollutants In mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the intensity of the test line is inversely proportional to the amount of analyte present in the sample. 95,96 Due to the diversity and selectivity of antibodies and the advantages of LFIA, this device has been used to determine a huge variety of analytes such as toxins, antibiotics in food, hormones in serum and urine, explosives, etc. [92][93][94][95] Conversely, other molecules can be attached on GNP (nucleic acids, enzymes, aptamers, etc.)…”
Section: Fluorescence Quenchingmentioning
confidence: 99%